ViDE: A Visual Data Extraction Environment for the Web - LI, Yi (Institutional Knowledge at Singapore Management University, 2001)
With the rapid growth of information on the Web, a means to combat information overload is critical. In this paper, we present ViDE (Visual Data Extraction), an interactive web data extraction environment that supports efficient hierarchical data wrapping of multiple web pages. ViDE has two unique features that differentiate it from other extraction mechanisms. First, data extraction rules can be easily specified in a graphical user interface that is seamlessly integrated with a web browser. Second, ViDE introduces the concept of grouping which unites the extraction rules for a set of documents with the navigational patterns that exist among them. This paper describes our initial development of the system.